1987
DOI: 10.1007/bf02623855
|View full text |Cite
|
Sign up to set email alerts
|

Defining conditions to promote the attachment of adult human colonic epithelial cells

Abstract: An improved method for the attachment and growth of normal human colonic epithelial cells from minute 1 to 3-mm3 biopsies has been developed. This yields four times as many cultured cells per biopsy than older methods, with a success rate of 97% in a series of 29 biopsies. Fetal bovine serum was eliminated from the medium, the medium pH was decreased to 6.7, the oxygen tension in the incubator was decreased to 3%, and the NCTC 168 medium was supplemented with ethanolamine, phosphoethanolamine, hydrocortisone, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Limited success has been reported for short-term culture (2-4 days) (Buset et al, 1987) and, in our hands, using culture techniques developed for premalignant adenoma cells, normal colonic epithelial cells behave similarly (Paraskeva and Williams, 1992). We therefore hypothesize that specific survival factors must be required by normal colonic epithelium.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Limited success has been reported for short-term culture (2-4 days) (Buset et al, 1987) and, in our hands, using culture techniques developed for premalignant adenoma cells, normal colonic epithelial cells behave similarly (Paraskeva and Williams, 1992). We therefore hypothesize that specific survival factors must be required by normal colonic epithelium.…”
Section: Discussionmentioning
confidence: 71%
“…Buset et al (1987) have reported the short-term culture (2-4 days) of normal colonic epithelial cells, and our experience with such primary cultures is similar (Paraskeva and Williams, 1992). Isolated colonocytes only survive for a few days in culture.…”
mentioning
confidence: 77%
“…29 30 There are also a few reports of short term normal cultures from adult colon tissues, but none in which the autofluorescence was studied. [31][32][33] In our present study, short term primary cell cultures of normal, hyperplastic, and dysplastic colonic epithelial cells obtained from biopsies were successfully established. Individual whole crypts were first isolated and imaged by confocal fluorescence microscopy (CFM).…”
mentioning
confidence: 96%
“…Another contemplated experiment will use molecular probes and proteomics that will clarify and characterize True cellular differentiation involves complex cellular interactions, [55][56][57] in which cell membrane junctions, extracellular matrices (e.g., basement membrane and ground substances) and soluble signals (endocrine, autocrine and paracrine) play important roles. [58][59][60][61] This process is also influenced by the spatial relationships (niche) of cells to each other. The responsiveness to exogenous mediators such as cytokines requires more than simply the presence of receptors.…”
Section: Discussionmentioning
confidence: 99%